Multielemental analysis of foliar tissue using ICP-MS - Alvarado1, Ana Lorena (2005)
An analytical method that allows the applicability of the hybrid technique ICP-MS to simultaneous multielemental analysis for foliar tissues was developed. The sample treatment, was optimized by digesting approximately 0.38 g of the foliar tissue, previously dried and screened to 0.5 mm mesh, with concentrated HNO3 until a clear product was obtained, after dilution with deionized water. Te was added as an internal standard. The quantification was done with an ICP-MS ELAN 6000, from PE-Sciex, under recommended instrumental conditions from the literature and other conditions optimized in the laboratory. The analytical performance parameters were satisfactory for the following elements: Al, As, Be, Cd, Co, Cr, Cu, Fe, Li, Mg, Mn, Mo, Na, Ni, P, Pb, Sb, Se, Tl, V and Zn. The detection limits were calculated by 2 methods, and they ranged between 1 μg l-1 for Cd and 40 μg l-1 for P. The accuracy of the proposed methodology was evaluated by determining the recovery percentage at 3 different concentration levels, also with a matrix with certified contents for some elements. Results from both assays included recoveries between 82% for Mg and 140% for Zn. The average values of sensibilities ranged from 157 cps (μg l-1)-1 for Be to 12272 cps (μg l-1)-1 for Tl. The precision of the method, as expressed by means of the relative standard deviation, was from 0.8% for As to 18.6% for Zn. It was shown also that results obtained for each element presented a linear behavior in the range of concentrations concerned.